Diagnosing decay mechanisms at the Porta Nocera Necropolis, Pompeii: the first step towards effective preventive conservation - Michette, M; Bichlmair, S; Kilian, R (Taylor and Francis, 2018)
Aspects of preventive conservation are central to the long-term preservation of archaeological sites such as Pompeii. Mitigating moisture ingress and its manifold effects on decay mechanisms such as salt degradation are of critical importance when planning durable conservation strategies. A suite of non-destructive techniques was used to diagnose decay mechanisms at an ancient tomb monument at the Porta Nocera Necropolis. Rising damp and salt contamination are shown to be actively contributing to on-going deterioration of the plaster surfaces. An existing shelter is shown to be inadequate in its protection. These initial results are used to inform a more in-depth, long-term survey as well as the design of a holistic preventive strategy.